Popular Proverbs and Political Culture in Libya - Mami, Mr>Mohammed (Dirasat in Economics and Business, 2002)
The literature on political culture shows that democratic practices and political participation depend Largely on the kind of political culture dominant in the society. It also shows that there is a correlation between democracy and participant political culture, while subject political culture and parochial political culture are associated with non —democratic practices and regimes. This paper represents an attempt to explore political culture in Libya aiming at discovering the effect of popular proverbs on its content. Through examining some of the popular proverbs dominant in the Libyan culture it is clear that these proverbs reflect the kind of attitudes associated with subject political culture, which is not conducive to political participation and democracy.